2022
DOI: 10.4103/jpbs.jpbs_555_21
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Knowledge, Attitude, and Practice with their Oral Health Status among Young Adults of Nursing Care

Abstract: Background: Nursing profession execute an imperative role in health promotion, disease, and injury prevention, providing care and assist in cure of patients with diverse age groups, and backgrounds both in individual and community settings. The study aimed to determine and compare the oral health knowledge, attitude, and practice (KAP) with oral health status among nursing students in Salem. Materials and Methods: A cross-sectional study was conducted on nursing student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…A dissociation was observed in the present study regarding the correlations between knowledge, attitude and practice. Indeed, it is generally acknowledged that better knowledge will translate into better attitude and practice 29 , 30 . Still, such a dissociation has been reported in medical students toward geriatric education, in whom improved knowledge did not translate into a better attitude 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A dissociation was observed in the present study regarding the correlations between knowledge, attitude and practice. Indeed, it is generally acknowledged that better knowledge will translate into better attitude and practice 29 , 30 . Still, such a dissociation has been reported in medical students toward geriatric education, in whom improved knowledge did not translate into a better attitude 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In another cross-sectional study, the knowledge of the relationship between oral-systemic disease and the examination or screening of the oral cavity among nursing graduates was found to be poor, owing to the lack of oral healthcare content in nursing curricula [29]. In general, female nurses were found to possess better knowledge about oral healthcare than males [43] (Figure 3). 40% of the schools [13].…”
Section: Knowledge Of Oral Healthcare Among Nursing Professionalsmentioning
confidence: 98%
“…Furthermore, interdisciplinary/interprofessional collaborative practice and educational programs were reported to improve the confidence levels and behaviors of nurses related to the promotion of oral health [17,18,[23][24][25][26][27]. Twenty-seven studies reported on the knowledge of oral healthcare among nursing professionals [13][14][15][16][17][18][19][20][21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Most studies reported (n=13) suboptimal or a lack of knowledge of oral healthcare among nurses [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Knowledge Of Oral Healthcare Among Nursing Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has established connections between knowledge, attitude, and practices [ 21 ]. While most research suggests that higher knowledge correlates with greater adoption of preventive measures and positive attitudes are associated with preventive behaviors [ 22 ], several studies have indicated a weak or no association between knowledge and practices [ 23 25 ]. Additionally, social and environmental determinants have been identified as key factors influencing individual health behaviors [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%